Mirogabalin Decreases Pain-like Behaviors by Inhibiting the Microglial/Macrophage Activation, p38MAPK Signaling, and Pronociceptive CCL2 and CCL5 Release in a Mouse Model of Neuropathic Pain - Renata Zajączkowska; Katarzyna Pawlik; Katarzyna Ciapała; Anna Piotrowska; Agata Ciechanowska; Ewelina Rojewska; Magdalena Kocot-Kępska; Wioletta Makuch; Jerzy Wordliczek; Joanna Mika (MDPI AG, 2023)
Neuropathic pain is a chronic condition that significantly reduces the quality of life of many patients as a result of ineffective pain relief therapy. For that reason, looking for new analgesics remains an important issue. Mirogabalin is a new gabapentinoid that is a specific ligand for the α2σ-1 and α2σ-2 subunits of voltage-gated calcium channels. In the present study, we compared the analgesic effect of pregabalin and mirogabalin in a neuropathic pain chronic constriction injury (CCI) of the sciatic nerve in a mouse model. The main purpose of our study was to determine the effectiveness of mirogabalin administered both once and repeatedly and to explain how the drug influences highly activated cells at the spinal cord level in neuropathy. We also sought to understand whether mirogabalin modulates the selected intracellular pathways (p38MAPK, ERK, JNK) and chemokines (CCL2, CCL5) important for nociceptive transmission, which is crucial information from a clinical perspective. First, our study provides evidence that a single mirogabalin administration diminishes tactile hypersensitivity more effectively than pregabalin. Second, research shows that several indirect mechanisms may be responsible for the beneficial analgesic effect of mirogabalin. This study reports that repeated intraperitoneally (i.p.) mirogabalin administration strongly prevents spinal microglia/macrophage activation evoked by nerve injury, slightly suppresses astroglia and neutrophil infiltration, and reduces the p38MAPK levels associated with neuropathic pain, as measured on Day 7. Moreover, mirogabalin strongly diminished the levels of the pronociceptive chemokines CCL2 and CCL5. Our results indicate that mirogabalin may represent a new strategy for the effective pharmacotherapy of neuropathic pain.